2020
DOI: 10.1016/j.hlpt.2020.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine, COVID-19, and disparities: Policy implications

Abstract: Highlights COVID-19 has resulted in a dramatic increase in the use of telemedicine but this could worsen disparities. We review recent telemedicine policy changes and their implications regarding disparities. We also discuss what systems can do to improve access to telemedicine and to best meet the needs of underserved patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
177
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(186 citation statements)
references
References 7 publications
8
177
0
1
Order By: Relevance
“…Immediate research interviews with families were not pursued because of the foreshadowed complex grief of those losing loved ones during the pandemic ( 20 , 37 ), particularly if their final connection was mediated by a screen. Although our findings resonate with disparities in technologic access and aptitude, we did not explore sociocultural, cognitive, or linguistic communication barriers; privacy concerns; or “webside manner” ( 28 , 38 ).…”
Section: Discussionmentioning
confidence: 50%
“…Immediate research interviews with families were not pursued because of the foreshadowed complex grief of those losing loved ones during the pandemic ( 20 , 37 ), particularly if their final connection was mediated by a screen. Although our findings resonate with disparities in technologic access and aptitude, we did not explore sociocultural, cognitive, or linguistic communication barriers; privacy concerns; or “webside manner” ( 28 , 38 ).…”
Section: Discussionmentioning
confidence: 50%
“…20,21 Concerns have been raised about virtual visits, including privacy, continuity of care and equity of implementation. 21,22 An Ontario pilot study of virtual care showed that, when provided with a choice of audio, video or text messaging on an integrated platform, more than 90% of visits occurred using asynchronous, secure text messaging followed by audio, yet there are no billing codes for text messaging. 28 Despite extensive use of virtual care in the COVID-19 pandemic, [23][24][25][26][27] the appropriate role of virtual care remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Also, communication with limited education or low‐literacy patients is not suitable. This limitation can reflect even more the disparities already evidenced by the COVID‐19 pandemic 7 . Besides, elderly patients could have difficulty in dealing with technology 8 .…”
Section: Discussionmentioning
confidence: 99%